Synthesis, crystal structure, and antidiabetic property of hydrazine functionalized Schiff base: 1,2-Di(benzylidene)hydrazine - Diyali, Nilankar; Chettri, Meena; De, Abhranil; Biswas, Bhaskar (European Journal of Chemistry, 2022)
Hydrazine functionalized Schiff base, 1,2-di(benzylidene)hydrazine has been synthesized through a condensation between hydrazine and benzaldehyde under reflux, and structurally characterized. The crystal structure analysis reveals that the Schiff base crystallizes in an orthorhombic crystal system with the Pbcn space group. Crystal data for C14H12N2: a = 13.130(2) Å, b = 11.801(2) Å, c = 7.5649(16) Å, V = 1172.1(4) Å3, Z = 4, T = 298.0(2) K, μ(MoKα) = 0.071 mm-1, Dcalc = 1.180 g/cm3, 10252 reflections measured (6.206° ≤ 2Θ ≤ 65.352°), 2027 unique (Rint = 0.0381, Rsigma = 0.0283) which were used in all calculations. The final R1 was 0.0627 (I > 2σ(I)) and wR2 was 0.2462 (all data). It is evident that the imine protons are intramolecularly locked with the imine-N bond, and the phenyl rings exist in anti orientation with respect to the =N-N= bond adopting a nearly planar conformation. The Schiff base grows a one-dimensional framework in the crystalline phase through long-distant C-H···π interaction. Hirshfeld surface and energy framework analyses have also been performed to understand the supramolecular forces and their contributions meticulously. The hydrazine functionalized Schiff base showed an excellent antidiabetic activity through α-amylase inhibitory assay relative to a standard compound, acarbose under an identical condition.